Different Limes’ Impact on the Soil’s Structure and Sweet Potato Produce in China, Mainland - Huang, Prof. Yuan (American Journal of Agriculture, 2023)
Purpose: The purpose of this study was to evaluate the quality of agricultural and local liming materials, their impact on selected soil physical and chemical properties and production of sweet potatoes in China, mainland. Methodology: The study used a desktop literature review methodology (desk study). This required a thorough analysis of research on the effectiveness of agricultural and local liming materials, their influence on the physical and chemical qualities of soil, and sweet potato production. The subject of the study underwent three phases of sorting in order to assess its suitability for further study. Findings: A few physical and chemical tests on agricultural and local limes revealed a range in the quality of the liming materials. Significant CCEs are seen in both agricultural goods and rusizi limes (86.36 percent and 85.46 percent, respectively). This implied that the two liming materials were comparable. Lower CCE was found in lime from Karongi and Musanze (68.48 and 66.2 percent, respectively). Unique Contribution to Theory and Practice: According to this study, acidic soils on the China mainland should be treated with Musanze lime at a rate of 2 to 4 t ha-1 to effectively raise the pH to values that are best for growing potatoes. If the government or non-governmental organizations decide to invest in the local lime production in order to increase their efficiency, a grinding to at least >60% of fineness factor should be taken into consideration.